Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1111/j.1751-1097.1992.tb04272.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo SPECTROPHOTOMETRIC EVALUATION OF NEOPLASTIC AND NON‐NEOPLASTIC SKIN PIGMENTED LESIONS. II: DISCRIMINANT ANALYSIS BETWEEN NEVUS AND MELANOMA

Abstract: Reflectance spectrophotometry from 420 to 780 nm on 31 primary melanoma and 31 benign nevi has been performed by using an external integrating sphere coupled to a spectrophotometer. Measurements show that reflectance spectra of melanoma and nevi manifest dissimilar patterns. From these spectra four variables, whose physical and/or physiological meanings remain to be investigated, have been derived. All of them are significantly different when compared between melanoma and nevi. A discriminant function between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 6 publications
0
32
0
1
Order By: Relevance
“…In studies with a somewhat greater number of patients, Marchesini et al 56 reported measurements of 31 primary melanomas and 31 benign nevi, which were made using a modified integrating sphere with a standard spectrophotometer over the spectral range 420-780 nm. The data were used to develop discriminant functions.…”
Section: © 2 0 0 4 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…In studies with a somewhat greater number of patients, Marchesini et al 56 reported measurements of 31 primary melanomas and 31 benign nevi, which were made using a modified integrating sphere with a standard spectrophotometer over the spectral range 420-780 nm. The data were used to develop discriminant functions.…”
Section: © 2 0 0 4 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…Diffuse reflectance measurements [6] offer one potential source of optical contrast, and have been applied to detect skin cancer, e.g. [7]. Similarly, spectroscopy and imaging of polarized light have been used to study epithelial tissues [8,9], including those involved in skin pathology [10].…”
Section: Introductionmentioning
confidence: 99%
“…Their experiments show that the wavelengths between 400 and 800 nm were highly significant to show the differences between the reflectance spectra of benign and malignant melanomas. Consequently, the authors report a discrimination between 31 primary melanoma and 31 benign lesions with a sensitivity of 90.3% and a specificity of 77.4%, a stepwise discriminate analysis of reflectance spectral features [35].…”
Section: State Of the Artmentioning
confidence: 99%